“What do mothers know about child sexual abuse?”: A qualitative investigation - KILIÇ, HASAN (My University, 2023)
© 2022 Elsevier LtdThe perceptions of mothers about child sexual abuse (CSA) and their levels of knowledge concerning the issue are critical for child abuse intervention and prevention. To date, however very little research has been conducted on this subject in the context of Turkey. Given that gap in the literature this study aims to evaluate the perceptions of Turkish mothers about CSA and recommend means of abuse prevention and intervention, and in doing so improve understanding of the topic. Descriptive phenomenological patterns derived from the qualitative research approach were used to shed light on the CSA perceptions of 15 Turkish mothers with children who were 3–6 years of age. The researchers interviewed the mothers with 11 structured questions and the resulting data were then analyzed with MAXQDA-18. Five main themes related to CSA emerged: defining CSA, as being aware of risk-factors, engaging in protective and preventative behaviour, recognizing cases of CSA and reacting to incidences of CSA. These findings are then discussed in terms of developments in the literature, as well as their implications, and recommendations are considered together with future research directions.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sosyoloji; Genel Sosyoloji ve Metedoloji; Eğitim; Social Sciences and Humanities; Psychology; Developmental Psychology; Sociology; General Sociology and Methodology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, GELİŞTİRME; SOSYOLOJİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, DEVELOPMENTAL; SOCIOLOGY; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Sosyoloji ve Siyaset Bilimi; Social Sciences & Humanities; Developmental and Educational Psychology; Sociology and Political Science; Child sexual abuse; Descriptive phenomenology; Mothering